The Role of PAI Lecturers in Character Education on Social Media: Character Education Analysis Study on the Status of PAI Lecturers on Facebook - Abdurrohman, Asep - (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
Nowadays, the importance of character education is not only in the form of face-to-face, but also in the form of Facebook social media statuses. This research aims to analyze the role of PAI lecturers when creating statuses on Facebook, which include character education. The primary sources for this research were 10 PAI lecturers in Banten, who had Facebook accounts. Data taken from October 2022 to October 2023. Meanwhile, secondary sources used in this research are books and research results that are relevant to the research. The sampling technique uses purposive sampling. Then, the data was analyzed using Content Analysis. Content Analysis is a scientific analysis of the message content of a communication. Technically, the scope of content analysis includes; classification of signs used in communication, using criteria as a basis for classification, and using certain analytical techniques to make predictions. There are three conditions in content analysis, namely; objectivity, systematic approach, and generalization. The results of the research show that the character education that PAI lecturers want to build on Facebook social media is very diverse. Starting from making netizens happy, becoming an entrepreneur, introspection, building future generations, building literacy, leaving behind something that is not useful, being able to work together in a variety of differences, to paying attention to social life in the form of spiritual education. Keywords: PAI Lecturers, Character Education, Facebook